Effects of Nabumetone and Dipyrone on Experimentally Induced Gastric Ulcers in Rats - Yildirim, Engin; Sagiroglu, Oya; Kilic, Fatma S.; Erol, Kevser (Springer/Plenum Publishers, 2013)
Nabumetone and dipyrone are non-acidic, nonsteroidal anti-inflammatory drugs. Both of them are known to have weak inhibitory effects of cyclooxygenases. Gastric side effects represent the most common adverse drug effects of the widely used nonsteroidal anti-inflammatory drugs. The gastric effects of these drugs may be comparable in experimental ulcer models. In the present study, the gastric ulcerogenic activity of nabumetone and dipyrone were investigated on stress- and diethyldithiocarbamate-induced experimental ulcer models by determining the ulcer index and gastric mucus secretion in rats. It was found that diethyldithiocarbamate increased both ulcer index and mucus secretion. Nabumetone inhibited dose-dependently the increase of diethyldithiocarbamate-induced mucus secretion. Dipyrone inhibited both stress- and diethyldithiocarbamate-induced ulcer index and mucus secretion. Nabumetone inhibited stress-induced ulcer index at 25-mg/kg dose but stimulated dose-dependently mucus secretion. These effects may be attributed to their non-acidic structures and weak inhibitory effects on gastric mucosal cyclooxygenases.
Keywords: nabumetone; dipyrone; diethyldithiocarbamate; experimental ulcer models; gastric mucus secretion; rat